2020
DOI: 10.14744/nci.2020.90532
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of SARS-CoV-2 in Istanbul: Sequencing findings from Epicenter of Pandemic in Turkey

Abstract: OBJECTIVE: Turkey is one of the latest countries that COVID-19 disease was reported, with the first case on March 11, 2020, and since then, Istanbul became the epicenter of the pandemic in Turkey. Here, we reveal sequences of the virus isolated from three different patients with various clinical presentations. METHODS: Nasopharyngeal swab specimens of the patients were tested positive for the COVID-19 by qRT-PCR. Viral RNA extraction was performed from the same swab samples. Amplicon based libraries were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Despite the overall stability of the SARS-CoV-2 genome, variants with mutations in S have spread globally (24)(25)(26)(27)(28)(29)(30)(31)(32). These mutations in S altered infectivity of cells (e.g., D614G (24)) or were located in the putative target domain of the HRC peptide (e.g., S943P).…”
Section: Main Textmentioning
confidence: 99%
“…Despite the overall stability of the SARS-CoV-2 genome, variants with mutations in S have spread globally (24)(25)(26)(27)(28)(29)(30)(31)(32). These mutations in S altered infectivity of cells (e.g., D614G (24)) or were located in the putative target domain of the HRC peptide (e.g., S943P).…”
Section: Main Textmentioning
confidence: 99%
“…The SNV A23403G (resulting in D614G variant in spike protein) is a major viral mutation that has been observed in the major European countries of Italy, Spain, France, as well as Middle Eastern regions of Turkey and Israel [16,[64][65][66]. Some studies suggest that this D614G variant of the S spike protein provides greater survival and transmission ability to the virus, however there need to be additional studies conducted to confirm these claims [64].…”
Section: Subtypes Including the A23403g/d614g Spike Protein Variantmentioning
confidence: 99%
“…It is difficult to draw a comparison between alternative methods since only a few multiplex amplicon-based papers to sequence the whole SARS-CoV-2 genome have been published [ 13 , 14 ]; in these studies, the panels were in the 150–400 bp amplicon range and designed to be used with MGI or Illumina platforms. When compared to a hybrid capture-based method, the authors in [ 13 ] observed low uniformity of coverage across different samples, although the amplicons method was more efficient than capture-based one for more challenging samples.…”
Section: Resultsmentioning
confidence: 99%